The Effectiveness of Restorative Justice Implementation in the Juvenile Criminal Justice System in Indonesia - Hutagalung, Tahi Saoloan (Jurnal Smart Hukum (JSH), 2023)
This study examines the effectiveness of restorative justice (RJ) in Indonesia’s juvenile criminal justice system. Employing a qualitative research approach, data were collected through literature review, statutory analysis, and in-depth interviews with legal practitioners, law enforcement officers, and child rights advocates. The findings indicate that while restorative justice has been formally recognized and partially implemented following the enactment of Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, several challenges hinder its optimal application. These include limited awareness, inconsistent law enforcement, and cultural barriers. Nevertheless, RJ has shown significant potential in reducing recidivism, promoting rehabilitation, and fostering community involvement. The study concludes with recommendations for strengthening the institutional framework, increasing public awareness, and enhancing the capacity of stakeholders to ensure the effective realization of restorative justice in Indonesia.